(untitled) (College of Basic Education Research Journal, 2025)
Research deals with educational reality in residential city of Bismayah. The study explains that educational reality in Bismayah focuses on primary stages of education: nursery, kindergarten, primary. then moves to incorporate intermediate and secondary facilities. Taken into consideration all urban services that Bismayah enjoys inside and outside its limits, not to forget to mention its geographical, urban capabilities and available spaces, all of above-mentioned facts integrate to create a foundation for future higher education centers such as institutes and colleges.